The Emergence of a General Theory of the Initiation and Strength of the Heartbeat - Victor A. Maltsev; Tatiana M. Vinogradova; Edward G. Lakatta (Elsevier, 2006)
Abstract.: Sarcoplasmic reticulum (SR) Ca2+ cycling, that is, the Ca2+ clock, entrained by externally delivered action potentials has been a major focus in ventricular myocyte research for the past 5 decades. In contrast, the focus of pacemaker cell research has largely been limited to membrane-delimited pacemaker mechanisms (membrane clock) driven by ion channels, as the immediate cause for excitation. Recent robust experimental evidence, based on confocal cell imaging, and supported by numerical modeling suggests a novel concept: the normal rhythmic heart beat is governed by the tight integration of both intracellular Ca2+ and membrane clocks. In pacemaker cells the intracellular Ca2+ clock is manifested by spontaneous, rhythmic submembrane local Ca2+ releases from SR, which are tightly controlled by a high degree of basal and reserve PKA-dependent protein phosphorylation. The Ca2+ releases rhythmically activate Na+/Ca2+ exchange inward currents that ignite action potentials, whose shape and ion fluxes are tuned by the membrane clock which, in turn, sustains operation of the intracellular Ca2+ clock. The idea that spontaneous SR Ca2+ releases initiate and regulate normal automaticity provides the key that reunites pacemaker and ventricular cell research, thus evolving a general theory of the initiation and strength of the heartbeat. Keywords:: cardiac excitation, contractility, pacemaker mechanism, calcium cycling, heart rate regulation